If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2(6 + -4y) = -9 3y + (6 * 2 + -4y * 2) = -9 3y + (12 + -8y) = -9 Reorder the terms: 12 + 3y + -8y = -9 Combine like terms: 3y + -8y = -5y 12 + -5y = -9 Solving 12 + -5y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -5y = -9 + -12 Combine like terms: 12 + -12 = 0 0 + -5y = -9 + -12 -5y = -9 + -12 Combine like terms: -9 + -12 = -21 -5y = -21 Divide each side by '-5'. y = 4.2 Simplifying y = 4.2
| 2x+46=30 | | 6x+24=6 | | 60/90=x/2 | | 7y+5=9x+2 | | n=f(t) | | 12x=60x | | 25x+8=7y+5 | | -2(2x+1)+4=10 | | r+4=4-6r-7r | | -3x^2+9x=7 | | -(3c-4)=37 | | 6n+7=8n-13 | | F(20)=b | | 9x+2=25x+8 | | 6t+3t=6 | | 10x+3=7x-39 | | -2(x+11)=6 | | .25y+3=-5 | | 5x+1=-2-8 | | -2.89=1.7 | | 6y+3(5y-19)-(y+2)=-142 | | 10=3+2 | | 24=-6m | | 0.25+.20x+1=2.25 | | F(a)=20 | | 2(x+2)-3(2x+5)=5 | | 7d=14 | | 2+3(p+3)=21 | | 3x-2=44 | | 4g+4=2g+12 | | 4b^2-49g^2=0 | | x^3+7x^2-25x-150=x^2 |